Stališča študentov medicine in zdravstvene nege Univerze v Ljubljani do medpoklicnega izobraževanja - Peterle, Helena (Obzornik zdravstvene nege, 2006)
Interprofessional education enables common education of students of different profiles. The purpose of it is better cooperation and communication inside health team and better quality of health care of patients, as well as better detection and solving of the problems, clarification of stereotypes and knowledge about different roles of different team rrcembers. Positive results are as well as on the part of the students as well as teachers and patients. Inquiry was filled in by 104 students, among them were 39 medical students and65 students of nursing care. The gathered results were processed quantitatively and qualitatively and revealed that all want to experience morecommon learning. The results revealed that foreign experiences should be used more often: in such a way the students would get some precious experienceand learn more about their future coworkers. This would enable them to get more knowledge and it would enhance their skills of professional and interpersonal level.
Keywords: ankete; education; Education, Continuing; izobraževanje; Izobraževanje nadaljevalno; medicina; medicine; medpoklicno sodelovanje; Questionnaires; student; Students, Medical; Students, Nursing; študenti; Študenti medicine; Študenti zdravstvene nege; zdravstvena nega